Early detection of C-reactive protein and von Willebrand factor levels in Malaysian patients with acute coronary syndrome - W.N, Tiong; Edmund, Ui Hang Sim; Alan, Yean Yip Fong (Medknow Publications and Media Pvt. Ltd, 2013)
Background: Diagnosing acute coronary syndrome (ACS) remains a challenge in patients presenting at early phase of hospitalization. We hypothesized that inflammatory markers of plaque rupture could accurately identifying ACS patients from stable coronary artery diseases (CAD). Materials and methods: The serum and peripheral blood gene expression levels of C-reactive protein (CRP) and von Willebrand factor (vWF) in multiethnic Malaysian patients (n = 7) admitted with early hospitalization of ACS was evaluated. Nine patients with stable coronary artery disease without previous history of ACS were enrolled as controls. Results: Serum and peripheral blood mRNA levels of CRP and vWF were significantly higher in ACS compared to control groups (P < 0.05). Conclusions: Elevated levels of these markers in ACS may reflect an acute phase response due to endothelial dysfunction. Both CRP and vWF may add to the list of useful markers for early detection of ACS in hospitals of developing countries.